Custodian Legal Culture - Enabling Multi-Stakeholder Research Collaborations Between Academia and Government in the UK - Aidinlis, Stergios (International Journal of Population Data Science, 2018)
Background Empirical studies suggest that some public bodies in England are very reluctant to grant access to administrative data for various purposes. This poster presents the conclusions drawn in my so-far research on the driving forces of administrative discretion in respect of data sharing for social research in the public interest in England. Objectives This poster aims to work towards answering a fundamental question for methodological models for engagement and research co-production between academia and government. This question is: what are the driving forces behind the exercise of data custodian discretion when it comes to deciding whether they will disclose it or not for research purposes? Methods (including data) First, this poster presents the findings of a qualitative case-study involving semi-structured interviews with individuals working for three different public bodies in England, two data providers and a body facilitating administrative data sharing for research. Second, it integrates a pilot survey which will aim to elicit the perspectives of ADR conference attendees, both admin data researchers and other stakeholders, on the crucial questions that revolve around the disclosure of data for research by different providers across the UK. Findings I propose a distinction between structural (e.g. the law/ infrastructural decision-making models) and cultural (e.g. perceptions of data ownership / trust-distrust in data sharing collaborators) influences, claiming that the latter are more salient in steering custodian discretion to share administrative data for research in practice than the former. I identify five main candidate cultural drivers and elaborate on them. Conclusions Without a sound socio-legal understanding of the driving forces of discretionary legal powers to share data on behalf of the providers, building bridges between them and the academic community in the interest of promoting social research in the public interest will remain a resilient challenge.